Current, future and potential use of mobile and wearable technologies and social media data in the ABCD study to increase understanding of contributors to child health. (August 2018) - Bagot, K.S.; Matthews, S.A.; Mason, M.; Squeglia, Lindsay M.; Fowler, J.; Gray, K.; Herting, M.; May, A.; Colrain, I.; Godino, J.; Tapert, S.; Brown, S.; et al.
Highlights: Novel mobile and wearable technologies to capture health-related data in children. Effects of place, social interactions, environment, activity and substance use. Potential in ABCD to advance understanding of contributors to development. Abstract: Mobile and wearable technologies and novel methods of data collection are innovating health-related research. These technologies and methods allow for multi-system level capture of data across environmental, physiological, behavioral, and psychological domains. In the Adolescent Brain Cognitive Development (ABCD) Study, there is great potential for harnessing the acceptability, accessibility, and functionality of mobile and social technologies for in-vivo data capture to precisely measure factors, and interactions between factors, that contribute to childhood and adolescent neurodevelopment and psychosocial and health outcomes. Here we discuss advances in mobile and wearable technologies and methods of analysis of geospatial, ecologic, social network and behavioral data. Incorporating these technologies into the ABCD study will allow for interdisciplinary research on the effects of place, social interactions, environment, and substance use on health and developmental outcomes in children and adolescents.